Membrane material for disposable bioreactor bag and preparation method of membrane material
By designing a bioreactor bag with a multi-layer film structure, the tensile strength and flexibility of the film are improved by using materials such as high-density polyethylene, linear low-density polyethylene and metallocene polyethylene, the tensile strength and flexibility of the film are solved, and the existing film materials are prone to deformation and tear, and the quality and service life of the product are improved.
Patent Information
- Application Number
- CN202411893303.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The tensile strength of the existing membrane materials for disposable bioreactor bags is insufficient, and it is easy to cause tensile deformation, tear, etc. during production and use, which affects the quality and service life of the product.
By reasonably setting the materials of each layer, a film material is designed that includes an outer surface protective layer, a first adhesive layer, a gas barrier layer, a second adhesive layer and a liquid contact layer in sequence from the outside to the inside. The surface protective layer uses high-density polyethylene, linear low-density polyethylene and metallocene polyethylene compositions, and materials such as maleic anhydride grafted polyethylene, maleic anhydride grafted ethylene propylene teremer rubber and polyethylene glycol modified carbon fiber-loaded carbon balls are added to improve the tensile strength and flexibility of the film material.
The high tensile strength and good kneading resistance of the membrane material are achieved, ensuring the stability and use effect of the bioreactor bag during production and use.
Smart Images

Figure CN119610830A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bioreactors, and in particular to a film material for a disposable bioreactor bag and a preparation method thereof. Background Art
[0002] Bioreactor bags are sterile mixing bags used in the biopharmaceutical field. They are mainly used in cell culture, fermentation, vaccine preparation and other processes. Bioreactor bags are a type of bioprocess bag, which usually has the advantages of small size, light weight, easy to carry and easy to operate, which helps to improve production efficiency and product quality. In the biopharmaceutical industry, bioreactor bags are widely used due to their flexibility and scalability, especially in situations where a sterile and controlled environment is required.
[0003] When preparing disposable bioreactor bags, multi-layer films are required, and disposable bioreactor bags have high requirements for multi-layer films. The multi-layer films are not only required to have barrier properties and water and solvent resistance, but also need to have high mechanical properties, etc., because disposable bioreactor bags may be pulled or rubbed by external forces during production and use. If they do not have high mechanical properties, they are easily damaged, thereby affecting the reaction performance of the disposable bioreactor bags.
[0004] The invention patent with application number 202211096737.9 discloses a multilayer film for bioprocess bags and its application. The multilayer film for bioprocess bags includes an outermost layer and an innermost layer, at least one barrier layer and at least one elastic tough layer are provided between the outermost layer and the innermost layer, and the average melting temperature of the outermost layer is at least 20°C higher than the average melting temperature of the innermost layer. The bioprocess bag has excellent strength, toughness, and rubbing resistance, and the outer surface of the multilayer film will not melt during the welding process. However, the tensile strength of the multilayer film for bioprocess bags is below 20MPa, which will make the bioprocess bags prone to tensile deformation, tearing, etc. during production and use, thereby affecting the quality and service life of the product.
[0005] Therefore, developing a disposable bioreactor bag film material with high tensile strength and high rubbing resistance can better ensure the performance of the disposable bioreactor bag. Summary of the invention
[0006] The object of the present invention is to provide a disposable bioreactor bag film material and a preparation method thereof. The present invention reasonably sets the material of each layer so that the obtained disposable bioreactor bag film material has high overall tensile strength while still maintaining high flexibility and strong barrier properties. It is not easy to be damaged during production and use, thereby effectively ensuring the use effect.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: A disposable bioreactor bag film material, comprising, from outside to inside, an outer protective layer, a first adhesive layer, a gas barrier layer, a second adhesive layer, and a liquid contact layer; The outer protective layer comprises the following raw materials in parts by weight: 70-90 parts of high-density polyethylene, 20-30 parts of linear low-density polyethylene, 15-20 parts of metallocene polyethylene, 5.5-8 parts of maleic anhydride grafted polyethylene, 3-5.5 parts of maleic anhydride grafted EPDM rubber, 1.2-1.6 parts of polyethylene glycol-modified carbon fiber-loaded carbon spheres, 1.5-2.2 parts of polyethylene glycol-modified calcium carbonate, and 0.1-0.15 parts of silane coupling agent.
[0008] Preferably, the gas barrier layer comprises the following raw materials in parts by weight: 40-60 parts of high-density polyethylene, 30-50 parts of linear low-density polyethylene, 10-15 parts of polyolefin elastomer, and 3-6 parts of ethylene-vinyl acetate copolymer; The material used for the first adhesive layer is ethylene-vinyl acetate copolymer or ethylene-acrylic acid copolymer; the material used for the second adhesive layer is ethylene-vinyl acetate copolymer or ethylene-acrylic acid copolymer; the material used for the liquid contact layer is linear low-density polyethylene.
[0009] Preferably, the thickness of the outer protective layer is 80~110μm; the thickness of the first adhesive layer is 15~30μm; the thickness of the gas barrier layer is 30~50μm; the thickness of the second adhesive layer is 15~30μm; and the thickness of the liquid contact layer is 150~200μm.
[0010] Preferably, the method for preparing polyethylene glycol-modified carbon fiber-loaded carbon spheres comprises the following steps: 1) Glucose, methyl cellulose and water are added to a reactor, heated to 70-80°C, stirred and mixed, and a precursor solution is obtained; then carbon fiber is added to the precursor solution, stirred and dispersed, the reactor is sealed, and the temperature is raised to 200-230°C for hydrothermal reaction for 5-7.5h, and then naturally cooled to room temperature, centrifuged, washed with water, and vacuum dried to obtain carbon fiber-loaded carbon spheres; 2) The carbon fiber-loaded carbon spheres are placed in an ethanol aqueous solution with a mass fraction of 20-30%, and then polyethylene glycol is added and stirred for 2-3 hours. The resulting mixture is vacuum dried and then dispersed to obtain polyethylene glycol-modified carbon fiber-loaded carbon spheres.
[0011] Preferably, in step 1), in the precursor solution, the mass fraction of glucose is 6-10%, and the mass fraction of methyl cellulose is 3-5%; the mass ratio of the carbon fiber to the precursor solution is 1:30-50; the length of the carbon fiber is 300-600 μm, and the diameter is 5-10 μm.
[0012] Preferably, in step 2), the mass ratio of the carbon fiber-loaded carbon spheres, polyethylene glycol and ethanol aqueous solution is 1:0.03-0.06:15-20; and the polyethylene glycol is polyethylene glycol 2000 or polyethylene glycol 3000.
[0013] Preferably, the preparation method of the polyethylene glycol-modified calcium carbonate comprises the following steps: Light calcium carbonate is placed in an ethanol aqueous solution with a mass fraction of 40-50%, and then polyethylene glycol is added and stirred for 4-5 hours. The resulting mixture is vacuum dried and then dispersed to obtain polyethylene glycol-modified calcium carbonate.
[0014] Preferably, the mass ratio of the light calcium carbonate, polyethylene glycol and ethanol aqueous solution is 1:0.03-0.05:10-15; the particle size of the light calcium carbonate is 400-600 mesh; and the polyethylene glycol is polyethylene glycol 2000 or polyethylene glycol 3000.
[0015] Preferably, the vacuum drying temperature is 70-80°C.
[0016] As a general inventive concept, the present invention provides a method for preparing a disposable bioreactor bag membrane, comprising the following steps: S1. Weigh each raw material according to the formula ratio of the surface protective layer; first, place the polyethylene glycol-modified carbon fiber-loaded carbon spheres, polyethylene glycol-modified calcium carbonate, and silane coupling agent in a high-speed mixer and mix for 1 to 2 hours, then add high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, maleic anhydride-grafted polyethylene, and maleic anhydride-grafted EPDM rubber and mix them evenly, and then place them in a twin-screw extruder for melt blending, extrusion, and granulation to obtain the material for the surface protective layer; S2. Add the material for the outer protective layer and the materials for the first adhesive layer, the gas barrier layer, the second adhesive layer, and the liquid contact layer into the extruder respectively, melt them respectively and convey them to the die head and the flow channel, and co-extrude them to prepare the disposable bioreactor bag film material.
[0017] The beneficial effects of the present invention are: The film material for the disposable bioreactor bag of the present invention has a liquid contact layer made of linear low-density polyethylene, and a main polymer material of the outer protective layer made of high-density polyethylene. The melting temperature of the outer protective layer is significantly higher than that of the innermost liquid contact layer, so that the outer protective layer of the film material will not melt during the heat sealing process, thereby effectively ensuring the heat sealing effect.
[0018] On this basis, when preparing the outer protective layer, the present invention uses high-density polyethylene, linear low-density polyethylene and metallocene polyethylene composition as the main substrate, and uses maleic anhydride grafted polyethylene and maleic anhydride grafted ethylene propylene rubber as compatibilizers and resin toughening agents, which can improve the strength and toughness of the outer protective layer. Further, the present invention adds an appropriate amount of polyethylene glycol-modified calcium carbonate to the outer protective layer as a nucleating agent to promote the crystallization of polyethylene and improve the crystal morphology and crystallinity of polyethylene, thereby effectively improving the flexibility and strength of the film. In addition, the calcium carbonate in the present invention is modified with polyethylene glycol, and then combined with the subsequent dry modification of silane coupling agent, the calcium carbonate can be highly dispersed in the polyethylene matrix, and the uniformly distributed calcium carbonate forms an efficient stress transfer network in the polyethylene. When the outer protective layer is subjected to external force, the generated stress can be dispersed and transferred through the stress transfer network, thereby improving the tensile strength and flexibility of the outer protective layer.
[0019] In order to further improve the tensile strength of the membrane material, the present invention also adds polyethylene glycol-modified carbon fiber loaded with carbon balls into the outer protective layer. The carbon fiber surface of this material is loaded with carbon balls, which can stabilize the carbon fiber in the polyethylene matrix. A small amount of carbon fiber addition can effectively improve the tensile strength of polyethylene, and the dispersion of carbon fiber loaded with carbon balls is improved compared with carbon fiber. Through polyethylene glycol modification and subsequent dry modification with silane coupling agent, the polyethylene glycol-modified carbon fiber loaded with carbon balls can be highly dispersed in the polyethylene matrix, so that the adverse effect of carbon fiber on the flexibility of polyethylene is less. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 It is a schematic structural diagram of the membrane material for a disposable bioreactor bag of the present invention; In the figure: 1. outer protective layer; 2. first adhesive layer; 3. gas barrier layer; 4. second adhesive layer; 5. liquid contact layer. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Preparation Example 1: The outer protective layer includes the following raw materials in parts by weight: 80 parts of high-density polyethylene, 22 parts of linear low-density polyethylene, 15 parts of metallocene polyethylene, 7 parts of maleic anhydride grafted polyethylene, 5 parts of maleic anhydride grafted EPDM rubber, 1.2 parts of polyethylene glycol-modified carbon fiber-loaded carbon spheres, 2 parts of polyethylene glycol-modified calcium carbonate, and 0.12 parts of silane coupling agent KH550.
[0024] The preparation method of polyethylene glycol modified carbon fiber loaded carbon spheres comprises the following steps: 1) Glucose, methyl cellulose and water were added to a reactor, heated to 80°C and stirred to obtain a precursor solution, in which the mass fraction of glucose was 8% and the mass fraction of methyl cellulose was 4%; then carbon fiber was added to the precursor solution, stirred and dispersed, the reactor was sealed, and the temperature was raised to 210°C for hydrothermal reaction for 6 hours, and then naturally cooled to room temperature, centrifuged, washed with water, and then vacuum dried at 80°C to obtain carbon fiber-loaded carbon spheres; wherein the mass ratio of carbon fiber to precursor solution was 1:40; the length of the carbon fiber was 300~600μm, and the diameter was 5~10μm.
[0025] 2) The carbon fiber-loaded carbon spheres were placed in a 25% mass fraction ethanol aqueous solution, and then polyethylene glycol 2000 was added and stirred for 3 hours. The resulting mixture was vacuum dried at 80°C and then dispersed to obtain polyethylene glycol-modified carbon fiber-loaded carbon spheres. The mass ratio of carbon fiber-loaded carbon spheres, polyethylene glycol and ethanol aqueous solution was 1:0.05:20.
[0026] The preparation method of polyethylene glycol modified calcium carbonate comprises the following steps: Light calcium carbonate was placed in a 50% ethanol aqueous solution, and then polyethylene glycol 2000 was added and stirred for 5 hours. The resulting mixture was vacuum dried and then dispersed to obtain polyethylene glycol-modified calcium carbonate. The mass ratio of light calcium carbonate, polyethylene glycol and ethanol aqueous solution was 1:0.03:12; the particle size of light calcium carbonate was 400-600 meshes.
[0027] The preparation method of the material for the surface protective layer comprises the following steps: weighing each raw material according to the formula ratio of the surface protective layer; firstly placing polyethylene glycol-modified carbon fiber-loaded carbon balls, polyethylene glycol-modified calcium carbonate, and silane coupling agent KH550 in a high-speed mixer and mixing for 2 hours, then adding high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, maleic anhydride-grafted polyethylene, and maleic anhydride-grafted EPDM rubber and mixing them evenly, and then placing them in a twin-screw extruder for melt blending, extrusion, and granulation to obtain the material for the surface protective layer.
[0028] Preparation Example 2: The outer protective layer includes the following raw materials in parts by weight: 90 parts of high-density polyethylene, 25 parts of linear low-density polyethylene, 15 parts of metallocene polyethylene, 5.5 parts of maleic anhydride grafted polyethylene, 5.5 parts of maleic anhydride grafted EPDM rubber, 1.5 parts of polyethylene glycol-modified carbon fiber loaded carbon spheres, 2 parts of polyethylene glycol-modified calcium carbonate, and 0.15 parts of silane coupling agent KH550.
[0029] The preparation method of polyethylene glycol modified carbon fiber loaded carbon spheres comprises the following steps: 1) Glucose, methyl cellulose and water were added to a reactor, and the mixture was heated to 75°C and stirred to obtain a precursor solution, in which the mass fraction of glucose was 10% and the mass fraction of methyl cellulose was 3%. Then, carbon fiber was added to the precursor solution, and after stirring and dispersion, the reactor was sealed and heated to 200°C for hydrothermal reaction for 7.5h, and then naturally cooled to room temperature, centrifuged, washed with water, and then vacuum dried at 75°C to obtain carbon fiber-loaded carbon spheres; wherein the mass ratio of carbon fiber to precursor solution was 1:50; the length of the carbon fiber was 300-600μm, and the diameter was 5-10μm.
[0030] 2) The carbon fiber-loaded carbon spheres were placed in a 30% ethanol aqueous solution, and then polyethylene glycol 3000 was added and stirred for 3 hours. The resulting mixture was vacuum dried at 75°C and dispersed to obtain polyethylene glycol-modified carbon fiber-loaded carbon spheres. The mass ratio of carbon fiber-loaded carbon spheres, polyethylene glycol and ethanol aqueous solution was 1:0.03:18.
[0031] The preparation method of polyethylene glycol modified calcium carbonate comprises the following steps: Light calcium carbonate is placed in a 50% ethanol aqueous solution, and then polyethylene glycol 2000 is added and stirred for 5 hours. The resulting mixture is vacuum dried and then dispersed to obtain polyethylene glycol-modified calcium carbonate. The mass ratio of light calcium carbonate, polyethylene glycol and ethanol aqueous solution is 1:0.04:12; the particle size of light calcium carbonate is 400-600 mesh.
[0032] The preparation method of the material for the surface protective layer comprises the following steps: weighing each raw material according to the formula ratio of the surface protective layer; firstly placing the polyethylene glycol-modified carbon fiber-loaded carbon spheres, polyethylene glycol-modified calcium carbonate, and silane coupling agent in a high-speed mixer and mixing for 1 hour, then adding high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, maleic anhydride-grafted polyethylene, and maleic anhydride-grafted EPDM rubber and mixing them evenly, and then placing them in a twin-screw extruder for melt blending, extrusion, and granulation to obtain the material for the surface protective layer.
[0033] Preparation Example 3: The outer protective layer includes the following raw materials in parts by weight: 70 parts of high-density polyethylene, 20 parts of linear low-density polyethylene, 18 parts of metallocene polyethylene, 6 parts of maleic anhydride grafted polyethylene, 4.5 parts of maleic anhydride grafted EPDM rubber, 1.2 parts of polyethylene glycol-modified carbon fiber loaded carbon spheres, 1.5 parts of polyethylene glycol-modified calcium carbonate, and 0.1 parts of silane coupling agent KH550.
[0034] The preparation method of polyethylene glycol modified carbon fiber loaded carbon spheres comprises the following steps: 1) Glucose, methyl cellulose and water were added to a reactor, heated to 70°C and stirred to obtain a precursor solution, in which the mass fraction of glucose was 6% and the mass fraction of methyl cellulose was 4%; then carbon fiber was added to the precursor solution, stirred and dispersed, the reactor was sealed, and the temperature was raised to 210°C for hydrothermal reaction for 7.5 hours, and then naturally cooled to room temperature, centrifuged, washed with water, and then vacuum dried at 75°C to obtain carbon fiber-loaded carbon spheres; wherein the mass ratio of carbon fiber to precursor solution was 1:45; the length of the carbon fiber was 300~600μm, and the diameter was 5~10μm.
[0035] 2) The carbon fiber-loaded carbon spheres were placed in a 20% ethanol aqueous solution, and then polyethylene glycol 3000 was added and stirred for 3 hours. The resulting mixture was vacuum dried at 70°C and dispersed to obtain polyethylene glycol-modified carbon fiber-loaded carbon spheres. The mass ratio of carbon fiber-loaded carbon spheres, polyethylene glycol and ethanol aqueous solution was 1:0.06:20.
[0036] The preparation method of polyethylene glycol modified calcium carbonate comprises the following steps: Light calcium carbonate was placed in a 40% ethanol aqueous solution, and then polyethylene glycol 2000 was added and stirred for 4 hours. The resulting mixture was vacuum dried and then dispersed to obtain polyethylene glycol-modified calcium carbonate. The mass ratio of light calcium carbonate, polyethylene glycol and ethanol aqueous solution was 1:0.03:10; the particle size of light calcium carbonate was 400-600 mesh.
[0037] The preparation method of the material for the outer protective layer is the same as that in Preparation Example 1.
[0038] Preparation Example 4: The outer protective layer includes the following raw materials in parts by weight: 85 parts of high-density polyethylene, 30 parts of linear low-density polyethylene, 20 parts of metallocene polyethylene, 8 parts of maleic anhydride grafted polyethylene, 3 parts of maleic anhydride grafted EPDM rubber, 1.6 parts of polyethylene glycol-modified carbon fiber-loaded carbon spheres, 2.2 parts of polyethylene glycol-modified calcium carbonate, and 0.15 parts of silane coupling agent KH550.
[0039] The preparation method of polyethylene glycol modified carbon fiber loaded carbon spheres comprises the following steps: 1) Glucose, methyl cellulose and water were added to a reactor, heated to 80°C and stirred to obtain a precursor solution, in which the mass fraction of glucose was 8% and the mass fraction of methyl cellulose was 5%; then carbon fiber was added to the precursor solution, stirred and dispersed, the reactor was sealed, and the temperature was raised to 230°C for hydrothermal reaction for 6.5h, then naturally cooled to room temperature, centrifuged, washed with water, and then vacuum dried at 75°C to obtain carbon fiber-loaded carbon spheres; wherein the mass ratio of carbon fiber to precursor solution was 1:30; the length of the carbon fiber was 300~600μm, and the diameter was 5~10μm.
[0040] 2) Place the carbon fiber loaded carbon spheres in a 30% ethanol aqueous solution, then add polyethylene glycol 3000 and stir for 2-3 hours, vacuum dry the resulting mixture at 80°C, and disperse to obtain polyethylene glycol-modified carbon fiber loaded carbon spheres. The mass ratio of carbon fiber loaded carbon spheres, polyethylene glycol and ethanol aqueous solution is 1:0.04:15.
[0041] The preparation method of polyethylene glycol modified calcium carbonate comprises the following steps: Light calcium carbonate is placed in a 40% ethanol aqueous solution, and then polyethylene glycol 3000 is added and stirred for 0.5 hours. The resulting mixture is vacuum dried and then dispersed to obtain polyethylene glycol-modified calcium carbonate. The mass ratio of light calcium carbonate, polyethylene glycol and ethanol aqueous solution is 1:0.05:15; the particle size of light calcium carbonate is 400-600 mesh.
[0042] The preparation method of the material for the outer protective layer is the same as that of Preparation Example 2.
[0043] Preparation Example 5: The gas barrier layer comprises the following raw materials in parts by weight: 60 parts of high-density polyethylene, 50 parts of linear low-density polyethylene, 10 parts of polyolefin elastomer, and 6 parts of ethylene-vinyl acetate copolymer.
[0044] The preparation method of the material for the gas barrier layer comprises the following steps: weighing each raw material according to the formula ratio of the gas barrier layer; placing high-density polyethylene, linear low-density polyethylene, polyolefin elastomer, and ethylene-vinyl acetate copolymer in a high-speed mixer and mixing them evenly, and then placing them in a twin-screw extruder for melt blending, extrusion, and granulation to obtain the material for the gas barrier layer.
[0045] Preparation Example 6: The gas barrier layer comprises the following raw materials in parts by weight: 40 parts of high-density polyethylene, 30 parts of linear low-density polyethylene, 15 parts of polyolefin elastomer, and 6 parts of ethylene-vinyl acetate copolymer.
[0046] The preparation method of the material for the gas barrier layer is the same as that of Preparation Example 5.
[0047] Embodiment 1: A membrane material for a disposable bioreactor bag, such as Figure 1 As shown, from outside to inside, it includes an outer protective layer 1, a first adhesive layer 2, a gas barrier layer 3, a second adhesive layer 4, and a liquid contact layer 5.
[0048] The material used for the outer protective layer is the material for the outer protective layer prepared in Preparation Example 1; the material used for the gas barrier layer is the material for the gas barrier layer prepared in Preparation Example 6; the material used for the first adhesive layer is ethylene-vinyl acetate copolymer; the material used for the second adhesive layer is ethylene-vinyl acetate copolymer; the material used for the liquid contact layer is linear low-density polyethylene.
[0049] The thickness of the outer protective layer is 90 μm; the thickness of the first adhesive layer is 20 μm; the thickness of the gas barrier layer is 50 μm; the thickness of the second adhesive layer is 20 μm; and the thickness of the liquid contact layer is 180 μm.
[0050] The method for preparing the membrane material for the disposable bioreactor bag of this embodiment comprises the following steps: The material for the outer protective layer and the materials for the first adhesive layer, the gas barrier layer, the second adhesive layer, and the liquid contact layer are respectively added to the extruder, melted and transported to the die head and the flow channel, and co-extruded to prepare the disposable bioreactor bag film material.
[0051] Embodiment 2: A disposable bioreactor bag film material comprises, from outside to inside, an outer protective layer 1, a first adhesive layer 2, a gas barrier layer 3, a second adhesive layer 4, and a liquid contact layer 5.
[0052] The material used for the outer protective layer is the material for the outer protective layer prepared in Preparation Example 3; the material used for the gas barrier layer is the material for the gas barrier layer prepared in Preparation Example 5; the material used for the first adhesive layer is ethylene-acrylic acid copolymer; the material used for the second adhesive layer is ethylene-acrylic acid copolymer; the material used for the liquid contact layer is linear low-density polyethylene.
[0053] The thickness of the outer protective layer is 110 μm; the thickness of the first adhesive layer is 25 μm; the thickness of the gas barrier layer is 30 μm; the thickness of the second adhesive layer is 25 μm; and the thickness of the liquid contact layer is 170 μm.
[0054] The method for preparing the membrane material for the disposable bioreactor bag of this embodiment is the same as that of Example 1.
[0055] Embodiment 3: A disposable bioreactor bag film material comprises, from outside to inside, an outer protective layer 1, a first adhesive layer 2, a gas barrier layer 3, a second adhesive layer 4, and a liquid contact layer 5.
[0056] The material used for the outer protective layer is the material for the outer protective layer prepared in Preparation Example 2; the material used for the gas barrier layer is the material for the gas barrier layer prepared in Preparation Example 6; the material used for the first adhesive layer is ethylene-vinyl acetate copolymer; the material used for the second adhesive layer is ethylene-vinyl acetate copolymer; the material used for the liquid contact layer is linear low-density polyethylene.
[0057] The thickness of the outer protective layer is 100 μm; the thickness of the first adhesive layer is 20 μm; the thickness of the gas barrier layer is 40 μm; the thickness of the second adhesive layer is 20 μm; and the thickness of the liquid contact layer is 150 μm.
[0058] The method for preparing the membrane material for the disposable bioreactor bag of this embodiment is the same as that of Example 1.
[0059] Embodiment 4: A disposable bioreactor bag film material comprises, from outside to inside, an outer protective layer 1, a first adhesive layer 2, a gas barrier layer 3, a second adhesive layer 4, and a liquid contact layer 5.
[0060] The material used for the outer protective layer is the material for the outer protective layer prepared in Preparation Example 4; the material used for the gas barrier layer is the material for the gas barrier layer prepared in Preparation Example 5; the material used for the first adhesive layer is ethylene-vinyl acetate copolymer; the material used for the second adhesive layer is ethylene-vinyl acetate copolymer; the material used for the liquid contact layer is linear low-density polyethylene.
[0061] The thickness of the outer protective layer is 95 μm; the thickness of the first adhesive layer is 15 μm; the thickness of the gas barrier layer is 50 μm; the thickness of the second adhesive layer is 15 μm; and the thickness of the liquid contact layer is 200 μm.
[0062] The method for preparing the membrane material for the disposable bioreactor bag of this embodiment is the same as that of Example 1.
[0063] Embodiment 5: A disposable bioreactor bag film material comprises, from outside to inside, an outer protective layer 1, a first adhesive layer 2, a gas barrier layer 3, a second adhesive layer 4, and a liquid contact layer 5.
[0064] The material used for the outer protective layer is the material for the outer protective layer prepared in Preparation Example 1; the material used for the gas barrier layer is the material for the gas barrier layer prepared in Preparation Example 5; the material used for the first adhesive layer is ethylene-acrylic acid copolymer; the material used for the second adhesive layer is ethylene-acrylic acid copolymer; the material used for the liquid contact layer is linear low-density polyethylene.
[0065] The thickness of the outer protective layer is 105 μm; the thickness of the first adhesive layer is 30 μm; the thickness of the gas barrier layer is 45 μm; the thickness of the second adhesive layer is 30 μm; and the thickness of the liquid contact layer is 180 μm.
[0066] The method for preparing the membrane material for the disposable bioreactor bag of this embodiment is the same as that of Example 1.
[0067] Embodiment 6: A disposable bioreactor bag film material comprises, from outside to inside, an outer protective layer 1, a first adhesive layer 2, a gas barrier layer 3, a second adhesive layer 4, and a liquid contact layer 5.
[0068] The material used for the outer protective layer is the material for the outer protective layer prepared in Preparation Example 3; the material used for the gas barrier layer is the material for the gas barrier layer prepared in Preparation Example 6; the material used for the first adhesive layer is ethylene-vinyl acetate copolymer or ethylene-acrylic acid copolymer; the material used for the second adhesive layer is ethylene-vinyl acetate copolymer or ethylene-acrylic acid copolymer; the material used for the liquid contact layer is linear low-density polyethylene.
[0069] The thickness of the outer protective layer is 100 μm; the thickness of the first adhesive layer is 20 μm; the thickness of the gas barrier layer is 40 μm; the thickness of the second adhesive layer is 20 μm; and the thickness of the liquid contact layer is 180 μm.
[0070] The method for preparing the membrane material for the disposable bioreactor bag of this embodiment is the same as that of Example 1.
[0071] Comparative Example 1: The difference from Example 6 is that the raw materials of the outer protective layer, polyethylene glycol-modified carbon fiber-loaded carbon spheres and polyethylene glycol-modified calcium carbonate, are replaced by the carbon fiber-loaded carbon spheres prepared in Preparation Example 3 and light calcium carbonate with a particle size of 400-600 mesh, respectively.
[0072] Comparative Example 2: The difference from Example 6 is that the raw material of the outer protective layer, polyethylene glycol-modified carbon fiber-loaded carbon spheres, is replaced by polyethylene glycol-modified carbon fiber.
[0073] The preparation method of polyethylene glycol modified carbon fiber comprises the following steps: placing carbon fiber in an ethanol aqueous solution with a mass fraction of 20%, then adding polyethylene glycol 3000, stirring for 3 hours, vacuum drying the obtained mixture at 70°C, and then dispersing to obtain polyethylene glycol modified carbon fiber. The mass ratio of carbon fiber, polyethylene glycol and ethanol aqueous solution is 1:0.06:20. The length of the carbon fiber is 300-600μm and the diameter is 5-10μm.
[0074] Comparative Example 3: Different from Example 6, the outer protective layer includes the following raw materials in parts by weight: 70 parts of high-density polyethylene, 20 parts of linear low-density polyethylene, 18 parts of metallocene polyethylene, 6 parts of maleic anhydride grafted polyethylene, 4.5 parts of maleic anhydride grafted EPDM rubber, 1.2 parts of polyethylene glycol-modified carbon fiber loaded carbon spheres, and 0.1 parts of silane coupling agent KH550.
[0075] Comparative Example 4: Different from Example 6, the outer protective layer includes the following raw materials in parts by weight: 70 parts of high-density polyethylene, 20 parts of linear low-density polyethylene, 18 parts of metallocene polyethylene, 6 parts of maleic anhydride grafted polyethylene, 4.5 parts of maleic anhydride grafted EPDM rubber, 1.5 parts of polyethylene glycol-modified calcium carbonate, and 0.1 parts of silane coupling agent KH550.
[0076] Performance Testing: 1. For the disposable bioreactor bag film prepared in Examples 1 to 6 and Comparative Examples 1 to 4, the tensile strength was tested according to ASTM D882, and the rubbing resistance was tested according to ASTM F392 (B method), and the number of pinholes generated in the film after rubbing was used to characterize the performance. The specific test results are shown in Table 1.
[0077] Table 1: Tensile strength / MPa Number of pinholes in the film after rubbing (pieces / 4 pieces) Example 1 33.2 1 Example 2 34.5 1 Example 3 32.3 0 Example 4 32.9 0 Example 5 34.2 1 Example 6 33.5 1 Comparative Example 1 28.5 4 Comparative Example 2 29.9 2 Comparative Example 3 26.7 6 Comparative Example 4 23.5 0 It can be seen from the above table that the disposable bioreactor bag film prepared by the method in the embodiment of the present invention has excellent tensile strength and rubbing resistance.
[0078] From the comparison between Example 6 and Comparative Example 1, it can be seen that if the carbon fiber-loaded carbon balls and light calcium carbonate are not modified, the tensile strength of the film will be significantly reduced, and the number of pinholes produced in the film after rubbing will also increase, that is, the modification of polyethylene glycol has a greater effect on improving the flexibility of the film.
[0079] From the comparison between Example 6 and Comparative Example 2, it can be seen that if the carbon balls are not loaded on the surface of the carbon fibers, the tensile strength of the membrane material is reduced, but the effect on the flexibility of the membrane material is small.
[0080] From the comparison between Example 6 and Comparative Example 3, it can be seen that if polyethylene glycol-modified calcium carbonate is not added when preparing the outer protective layer, not only the tensile strength is significantly reduced, but also the rubbing resistance of the film material is significantly reduced.
[0081] From the comparison between Example 6 and Comparative Example 4, it can be seen that when polyethylene glycol-modified carbon fiber loaded carbon balls are not added to the membrane material, the tensile strength of the membrane material will be significantly reduced. Polyethylene glycol-modified carbon fiber loaded carbon balls are very important for improving the tensile strength of the surface protective layer.
[0082] 2. For the disposable bioreactor bag films prepared in Examples 1 to 6 and Comparative Examples 1 to 4, the oxygen permeability was tested according to GB / T 19789, the water vapor permeability was tested according to GB / T 10004, and the transparency was tested using a light transmittance meter. The specific test results are shown in Table 2.
[0083] Table 2: <![CDATA[Oxygen permeability / (mL / m 2 ·d·atm)]]> <![CDATA[Water vapor transmission rate / (mL / m 2 ·d·atm)]]> transparency / % Example 1 0.08 0.5 92 Example 2 0.07 0.6 91 Example 3 0.07 0.4 92 Example 4 0.06 0.6 92 Example 5 0.08 0.5 91 Example 6 0.06 0.5 91 Comparative Example 1 0.07 0.5 91 Comparative Example 2 0.08 0.6 91 Comparative Example 3 0.07 0.5 92 Comparative Example 4 0.07 0.5 93 It can be seen from Table 2 that the disposable bioreactor bag film materials prepared in the embodiments of the present invention and the comparative examples have high barrier properties and high transparency. Among them, it can be seen from the comparison between Example 6 and Comparative Example 4 that the addition of polyethylene glycol-modified carbon fiber-loaded carbon spheres has some adverse effects on the transparency of the film material.
[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A membrane material for a disposable bioreactor bag, characterized in that: The disposable bioreactor bag film material comprises, from outside to inside, an outer protective layer, a first adhesive layer, a gas barrier layer, a second adhesive layer, and a liquid contact layer; The outer protective layer comprises the following raw materials in parts by weight: 70-90 parts of high-density polyethylene, 20-30 parts of linear low-density polyethylene, 15-20 parts of metallocene polyethylene, 5.5-8 parts of maleic anhydride grafted polyethylene, 3-5.5 parts of maleic anhydride grafted EPDM rubber, 1.2-1.6 parts of polyethylene glycol-modified carbon fiber-loaded carbon spheres, 1.5-2.2 parts of polyethylene glycol-modified calcium carbonate, and 0.1-0.15 parts of silane coupling agent.
2. The disposable bioreactor bag membrane material according to claim 1, characterized in that: The gas barrier layer comprises the following raw materials in parts by weight: 40-60 parts of high-density polyethylene, 30-50 parts of linear low-density polyethylene, 10-15 parts of polyolefin elastomer, and 3-6 parts of ethylene-vinyl acetate copolymer; The material used for the first adhesive layer is ethylene-vinyl acetate copolymer or ethylene-acrylic acid copolymer; the material used for the second adhesive layer is ethylene-vinyl acetate copolymer or ethylene-acrylic acid copolymer; the material used for the liquid contact layer is linear low-density polyethylene.
3. The disposable bioreactor bag membrane material according to claim 1, characterized in that: The thickness of the outer protective layer is 80-110 μm; the thickness of the first adhesive layer is 15-30 μm; the thickness of the gas barrier layer is 30-50 μm; the thickness of the second adhesive layer is 15-30 μm; and the thickness of the liquid contact layer is 150-200 μm.
4. The disposable bioreactor bag membrane material according to claim 1, characterized in that: The preparation method of the polyethylene glycol modified carbon fiber loaded carbon spheres comprises the following steps: Glucose, methyl cellulose and water are added to a reactor, heated to 70-80°C and stirred to obtain a precursor solution; then carbon fiber is added to the precursor solution, stirred and dispersed, the reactor is sealed, and the temperature is raised to 200-230°C for hydrothermal reaction for 5-7.5h, and then naturally cooled to room temperature, centrifuged, washed with water, and vacuum dried to obtain carbon fiber-loaded carbon spheres; The carbon fiber-loaded carbon spheres are placed in an ethanol aqueous solution with a mass fraction of 20-30%, and then polyethylene glycol is added and stirred for 2-3 hours. The resulting mixture is vacuum dried and then dispersed to obtain polyethylene glycol-modified carbon fiber-loaded carbon spheres.
5. The disposable bioreactor bag membrane material according to claim 4, characterized in that: In step 1), in the precursor solution, the mass fraction of glucose is 6-10%, and the mass fraction of methyl cellulose is 3-5%; the mass ratio of the carbon fiber to the precursor solution is 1:30-50; the length of the carbon fiber is 300-600 μm, and the diameter is 5-10 μm.
6. The disposable bioreactor bag membrane material according to claim 1, characterized in that: In step 2), the mass ratio of the carbon fiber-loaded carbon spheres, polyethylene glycol and ethanol aqueous solution is 1:0.03-0.06:15-20; the polyethylene glycol is polyethylene glycol 2000 or polyethylene glycol 3000.
7. The disposable bioreactor bag membrane material according to claim 1, characterized in that: The preparation method of the polyethylene glycol-modified calcium carbonate comprises the following steps: Light calcium carbonate is placed in an ethanol aqueous solution with a mass fraction of 40-50%, and then polyethylene glycol is added and stirred for 4-5 hours. The resulting mixture is vacuum dried and then dispersed to obtain polyethylene glycol-modified calcium carbonate.
8. The disposable bioreactor bag membrane material according to claim 7, characterized in that: The mass ratio of the light calcium carbonate, polyethylene glycol and ethanol aqueous solution is 1:0.03-0.05:10-15; the particle size of the light calcium carbonate is 400-600 mesh; and the polyethylene glycol is polyethylene glycol 2000 or polyethylene glycol 3000.
9. The disposable bioreactor bag membrane according to any one of claims 4 to 8, characterized in that: The vacuum drying temperature is 70-80°C.
10. A method for preparing a disposable bioreactor bag membrane according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh each raw material according to the formula ratio of the surface protective layer; first, place the polyethylene glycol-modified carbon fiber-loaded carbon spheres, polyethylene glycol-modified calcium carbonate, and silane coupling agent in a high-speed mixer and mix for 1 to 2 hours, then add high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, maleic anhydride-grafted polyethylene, and maleic anhydride-grafted EPDM rubber and mix them evenly, and then place them in a twin-screw extruder for melt blending, extrusion, and granulation to obtain the material for the surface protective layer; S2. Add the material for the outer protective layer and the materials for the first adhesive layer, the gas barrier layer, the second adhesive layer, and the liquid contact layer into the extruder respectively, melt them respectively and convey them to the die head and the flow channel, and co-extrude them to prepare the disposable bioreactor bag film material.
Citation Information
Patent Citations
Multilayer films for bioprocess bags and their applications
CN115556448B
Method for preparing hydrothermal carbon layer on surfaces of carbon fibers and application of hydrothermal carbon layer
CN108004767A
ULDPE-containing multi-layer co-extrusion disposable biotechnological bag membrane material and preparation method thereof
CN113306244A
Single-Use Bioprocessing Bag for Growing Cell Media, and Multilayer Film
US20230060563A1
Biocidal sachet for food safety
WO2015130992A1